Poppy Harmon and the shooting star [large type] - Hollis, Lee (A Desert Flowers mystery ;, 2023)
"Poppy never planned on speaking to her old acting rival Serena Saunders again, let alone accepting her as a client. But familiar drama barges back into her life when Serena requests an urgent background check on Ned Boyce, her fiancé, before tying the knot. And the flighty film star is behaving out of character by wishing to start over with Poppy--this time as friends . . . Wealthy, connected, and the owner of a breathtaking mountaintop home, Ned seems like the most unlikely private investigation subject in Palm Springs. Poppy no sooner thinks she's nailed down her latest assignment than Serena is caught holding a smoking gun over a stranger's dead body . . . With Serena claiming self-defense and the wedding fast approaching, the Desert Flowers team must summon their showbiz talents to expose the truth about the unknown victim. But as her former enemy finds herself in another devastating position, only Poppy can determine who's innocent and who's ready to smile for their mug shot."--